THE EFFECT OF FIRM PERFORMANCE, ERM DISCLOSURE, AND RISK MANAGEMENT COMMITTEE ON SUSTAINABLE GROWTH RATE - Handoyo, Jason Jonathan; Handoko, Jesica (Berkala Akuntansi dan Keuangan Indonesia, 2025)
Sustainability, or a firm's ability to survive long-term, is a primary goal for stakeholders. Two main factors are thought to influence a firm's sustainable growth: first, firm performance, and second, sound risk management to mitigate the negative impacts of unexpected events beyond the firm's control. This study aims to examine the influence of firm performance (which includes financial performance, including profitability, liquidity, capital structure, and environmental performance), as well as the influence of enterprise risk management disclosure and Risk Management Committee on sustainable growth rates. This study is a quantitative study with hypothesis testing. The objects of this study were all manufacturing companies listed on the Indonesia Stock Exchange for the period 2021-2023. The analytical technique used was multiple regression analysis. The results of this study found that financial performance has a positive influence on sustainable growth rates, while environmental performance has a negative influence on sustainable growth rates. Enterprise risk management disclosure and Risk Management Committee were not found to have an effect on sustainable growth rates. This study implies the importance of management paying attention to performance achievements, which should not only include financial performance but also non-financial and environmental performance in fostering sustainable growth rates.